Volume 3B: 47th Design Automation Conference (DAC) 2021
DOI: 10.1115/detc2021-66758
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Topology Optimization With Gaussian Process Regression Models

Abstract: Multiscale topology optimization (MSTO) is a numerical design approach to optimally distribute material within coupled design domains at multiple length scales. Due to the substantial computational cost of performing topology optimization at multiple scales, MSTO methods often feature subroutines such as homogenization of parameterized unit cells and inverse homogenization of periodic microstructures. Parameterized unit cells are of great practical use, but limit the design to a pre-selected cell shape. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our literature review revealed that researchers mainly used machine learning and deep learning algorithms for design optimization in this phase. In addition to these, we also observed: four optimization methods, which used a multi-objective genetic algorithm for optimal material selection (Zhou et al 2009) and simulation-based optimization (Owoyele et al 2021), Gaussian process regression for topology optimization (Najmon et al 2021), and Bayesian optimization for improving geometric parameters (Coulter et al 2022); one probabilistic method involving multiscale Gaussian process for multi-physics simulation-based optimization (Sarkar et al 2019); and one novel framework for modeling detailed design knowledge using a structural-behavior-function (SBF) model and a genetic programming approach (Chen et al 2013).…”
Section: Ai In Detailed Designmentioning
confidence: 99%
“…Our literature review revealed that researchers mainly used machine learning and deep learning algorithms for design optimization in this phase. In addition to these, we also observed: four optimization methods, which used a multi-objective genetic algorithm for optimal material selection (Zhou et al 2009) and simulation-based optimization (Owoyele et al 2021), Gaussian process regression for topology optimization (Najmon et al 2021), and Bayesian optimization for improving geometric parameters (Coulter et al 2022); one probabilistic method involving multiscale Gaussian process for multi-physics simulation-based optimization (Sarkar et al 2019); and one novel framework for modeling detailed design knowledge using a structural-behavior-function (SBF) model and a genetic programming approach (Chen et al 2013).…”
Section: Ai In Detailed Designmentioning
confidence: 99%